Human cargo a journey among refugees - Moorehead, Caroline (Henry Holt, 2005)
A portrait of the lives of today's refugees cites an alarming percentage of the world's population that has been forced to abandon home and family in order to survive, sharing the personal stories of people struggling to make lives for themselves in such areas as Cairo, Lebanon, and Australia. By the author of Gellhorn. An arresting portrait of the lives of today's refugees and a searching look into their future The word refugee is more often used to invoke a problem than it is to describe a population of millions of people forced to abandon their homes, possessions, and families in order to find a place where they may, quite literally, be allowed to live. In spite of the fact that refugees surround us-the latest UN estimates suggest that 20 million of the world's 6.3 billion people are refugees-few can grasp the scale of their presence or the implications of their growing numbers. Caroline Moorehead has traveled for nearly two years and across four continents to bring us their unforgettable stories. In prose that is at once affecting and informative, we are introduced to the men, women, and children she meets as she travels to Cairo, Guinea, Sicily, the U.S./Mexico border, Lebanon, England, Australia, and Finland. She explains how she came to work and for a time live among refugees, and why she could not escape the pressing need to understand and describe the chain of often terrifying events that mark their lives. Human Cargo is a work of deep and subtle sympathy that completely alters our understanding of what it means to have and lose a place in the world.